ON THE FORMATION OF PERIDOTITE-DERIVED OS-RICH PGE ALLOYS - Brenker F.E.; Meibom A.; Frei R. (My University, 2003)
Osmium-rich Pt group element (PGE) alloys occur worldwide in association with chromite in ultramafic (peridotite) complexes. It has been suggested that these Os-rich alloys formed under extreme P-T conditions in the lowermost mantle, before the metallic core of the Earth formed, or later, in the outer core, and have been transported to the upper mantle as xenoliths in deep-rooted mantle plumes.